ANALYSIS OF EFFECT OF EDUCATION LEVEL AND EXPERIENCE LEVEL TO PRODUCTIVITY ACCOUNT EXECUTIVE IN THE SALES DEPARTMENT MNC MEDIA (OKEZONE.COM) - Nanda Ekawati (Politeknik Negeri Jakarta, 2017)
AbstractAccount executive is human resources which seek revenue for the company. Given the importance of the role of account executive, it should be noted also factors that affect productivity such as education level account executive who owned and had experiences. The problem in this research is to determine how much influence the level of education and experience on the productivity of account executives in MNC Media (Okezone.com). The purpose of this study was to analyze whether there is influence between the level of education, experience and productivity account executive. A population of 30 people account executive, used as a sample of 30 people taken from the business unit MNC Media others with the same title. The method used was a questionnaire. The conclusion is obtained no positive and significant influence between variables either jointly or individually after T test and F test Multiple regression analysis has also been done with the coefficient of educational level (X1) of 0.521 which means that every increase of 1 unit variable educational level (X1) it will raise the value of the variable productivity (Y) amounted to 0.521 units assuming other independent variables remain valuable. So is the experience coefficient (X2) of 0.614. The coefficient of determination at variable levels of education and experience together show the result in the amount of 50.6%, which means that the influence exerted by the level of education and experience to work productivity in this study was 50.6%, while 49.4% of them are affected by other factors that are not observed in this study.Key words: effect, education level, experience level, productivity, account executive